Discover bugs (NPP Bath, 2009)
"Discover Bugs," published by North Parade Publishing Ltd. in 2010. This 45-page hardcover is part of the "Wonders of Learning" series and offers an educational exploration into the world of insects. Readers can learn about various bugs, including bees, grasshoppers, and butterflies, and discover intriguing facts such as why spiders aren't classified as bugs, how bees produce honey, and the resilience of cockroaches.